Hydration and interactions between C3S and C3A polymorphs in the presence of different calcium sulfates - Andrade Neto, José da Silva (2021)
Calcium sulfate is an important constituent in Portland cement nowadays. It is used to control the setting time of Portland cement. However, many questions about the role of calcium sulfate on the cement phases (C3A and C3S) hydration and its mechanisms persist. A critical overview of the effect of sulfates on Portland cement hydration and properties is presented here in a review manuscript form. In this sense, several knowledge gaps, such as the influence of C3S and C3A polymorphs and the calcium sulfate composition on the sulfate balance in Portland cement, were identified. To address some of the questions identified in the review three different experimental studies were executed. The first one was focused to understand how gypsum accelerates the C3S hydration and whether aluminum incorporated in its structure plays an essential role or not. The effects of gypsum on the hydration of C3S and aluminum-doped C3S (Al-C3S) hydration were assessed. Calorimetry, XRD, TGA, and 27Al and 29Si MAS-NMR were performed to analyze gypsum’s influence on the hydration of C3S and Al-C3S. The results showed that the inclusion of gypsum retarded the initial hydration (first 3 h) for both C3S and Al-C3S, due to the interaction between the sulfate ions and C3S. In contrast, gypsum enhanced the hydration of both C3S and Al-C3S afterward. This acceleration effect occurred earlier for the Al-C3S due to the removal of aluminum from the solution. However, this is not the main mechanism behind the acceleration of C3S by gypsum, which mainly results from changes in C-S-H morphology and increases in the ionic strength. Secondly, the mechanism responsible for the higher reactivity of orthorhombic C3A (ort-C3A) in sulfate-containing solutions, compared with cubic C3A (cb-C3A), which was previously related to either the difference in crystal structure or the sodium in ort-C3A pore solution were investigated. The hydration of cbC3A (in water and NaOH solution) and Na-doped ort-C3A in the presence of gypsum and hemihydrate were analyzed using isothermal calorimetry, in-situ XRD, TGA, SEM, and rheological tests. The results showed that NaOH accelerated the hydration of cb-C3A, but ortC3A still presented a higher hydration rate. Ort-C3A pastes revealed more and larger ettringite crystals at 30-120 minutes, resulting in higher viscosities and yield stresses than cb-C3A pastes. The replacement of gypsum with hemihydrate accelerated ort-C3A hydration but retarded cbC3A hydration. Overall, the higher reactivity of ort-C3A is related to differences in crystal structure rather than the sodium in pore solution. Finally, the hydration of three-phase systems (C3S-C3A-calcium sulfate) was analyzed. Two C3S (T1 pure C3S and M1 aluminum-doped C3S), two C3A polymorphs (cubic and orthorhombic), and two calcium sulfates (gypsum and hemihydrate) were evaluated. For each system, the hydration of four different SO3 contents was evaluated by calorimetry. From the calorimetry results, a 1.5 wt.% SO3 content was fixed, and the mixtures were evaluated by in-situ XRD and TGA. The C3S type was the factor that most affected the sulfate balance of the systems. The mixes with Al-C3S presented higher ettringite formation in the first hours, resulting in much earlier sulfate depletions when compared to the mixes with C3S. The mixes with ort-C3A also presented faster sulfate depletions, due to its higher reactivity compared with cb-C3A. Finally, the replacement of gypsum by hemihydrate, also resulted in faster sulfate depletions, which is the consequence of the higher solubility of hemihydrate.